Cytokines and Chemokines Modulation of Itch. (15th July 2022) - Du, Li-Xia; Zhu, Jian-Yu; Mi, Wen-Li
Highlights: Cytokines participant in the pathogenesis of itch in both human and rodents. Some cytokines directly activate sensory neurons and act as pruritogens. Chemokines modulate pathogenesis of itch in the peripheral and central level. Abstract: Itch (pruritus) is a common cutaneous symptom widely associated with many skin complaints, and chronic itch can be a severe clinical problem. The onset and perpetuation of itch are linked to cytokines, such as interleukin (IL)-31, IL-4, IL-13, IL-33, thymic stromal lymphopoietin, and tumor necrosis factor-alpha, and chemokines, such as chemokine (C–C motif) ligand 2 and C–X–C motif chemokine ligand 10. This review highlights research that has attempted to determine the attributes of various cytokines and chemokines concerning the development and modulation of itch. Through such research, clinical approaches targeting cytokines and/or chemokines may arise, which may further the development of itch therapeutics.